2012
DOI: 10.1105/tpc.112.101014
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Regulates the Arabidopsis Floral Transition through miR156-Targeted SQUAMOSA PROMOTER BINDING–LIKE Transcription Factors

Abstract: Gibberellin (GA), a diterpene hormone, plays diverse roles in plant growth and development, including seed germination, stem elongation, and flowering time. Although it is known that GA accelerates flowering through degradation of transcription repressors, DELLAs, the underlying mechanism is poorly understood. We show here that DELLA directly binds to microRNA156 (miR156)-targeted SQUAMOSA PROMOTER BINDING-LIKE (SPL) transcription factors, which promote flowering by activating miR172 and MADS box genes. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
361
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(368 citation statements)
references
References 73 publications
3
361
1
3
Order By: Relevance
“…Further genetic analysis suggests that the early-flowering phenotype of GbWRKY1-overexpressing Arabidopsis depends on the expression of SOC1 (Fig. 4E), which participates in DELLA-mediated flowering time control (Yu et al, 2012). Interestingly, wildtype and GbWRKY1-RNAi plants did not show observable differences in terms of plant morphology and sensitivity to PAC (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further genetic analysis suggests that the early-flowering phenotype of GbWRKY1-overexpressing Arabidopsis depends on the expression of SOC1 (Fig. 4E), which participates in DELLA-mediated flowering time control (Yu et al, 2012). Interestingly, wildtype and GbWRKY1-RNAi plants did not show observable differences in terms of plant morphology and sensitivity to PAC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[See online article for color version of this figure. ] A recent study demonstrated that DELLA proteins modulate flowering time by a direct binding of RGA to SQUAMOSA PROMOTER BINDING-LIKE (SPL) to attenuate the SPL transcriptional activities of SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1; Yu et al, 2012). Our results demonstrate that the expression of SOC1 is consistently up-regulated by the overexpression of GbWRKY1 during seedling development (Fig.…”
Section: Gbwrky1 Negatively Regulates the Ja Signaling Pathwaymentioning
confidence: 99%
“…Third, it may be that other unrelated proteins repress flowering in addition to GNC and GNL in the absence of GA. In this regard, it is interesting that the protein SPL9 was recently identified as a DELLA-controlled flowering time regulator in Arabidopsis and that GA was recently described to promote the expression of the SPL genes SPL3, SPL4, and SPL5 in a SOC1-dependent manner (Wu et al, 2009;Jung et al, 2012;Yu et al, 2012). Thus, DELLA repression of SPL gene expression and SPL protein activity could potentially delay flowering in ga1 in parallel to GNC and GNL.…”
Section: Discussionmentioning
confidence: 99%
“…SPL gene expression is inhibited by DELLA proteins (SI Appendix, Fig. S5), so a decrease in them could result in increased SPL expression (36). However, transcripts of genes encoding two major DELLA proteins (RGL1 and RGA) were unchanged or elevated in DOG1-RNAi leaves (SI Appendix, Fig.…”
Section: Dog1mentioning
confidence: 99%